Legal and Institutional Functionality in the Protection of Women – Victims of Domestic Violence in the Republic of Macedonia – Present Situation and Future Perspectives - Professor, Zorica Saltirovska; Sunchica Dimitrijoska, Professor (European Journal of Social Science Education and Research, 2018)
Gender-based violence is a form of discrimination that prevents women from enjoying the rights and liberties on an equal level with men. Inevitably, domestic violence shows the same trend of victimizing women to such a degree that the term “domestic violence” is increasingly becoming synonymous with “violence against women”. The Istanbul Convention defines domestic violence as "gender-based violence against women", or in other words "violence that is directed against a woman because she is a woman or that affects women disproportionately." The situation is similar in the Republic of Macedonia, where women are predominantly victims of domestic violence. However, the Macedonian legal framework does not define domestic violence as gender-based violence, and thus it does not define it as a specific form of discrimination against women. The national legislation stipulates that victims are to be protected in both a criminal and a civil procedure, and the Law on Prevention and Protection from Domestic Violence determines the actions of the institutions and civil organizations in the prevention of domestic violence and the protection of victims. The system for protection of victims of domestic violence closely supports the Law on Social Protection and the Law on Free Legal Aid, both of which include provisions on additional assistance for women victims of domestic violence. However, the existing legislation has multiple deficiencies and does not allow for a greater efficacy in implementing the prescribed measures for the protection of victims of domestic violence. For this reason, as well as due to the inconsistent implementation of legal solutions of this particular issue, the civil sector is constantly expressing their concern about the increasingly wider spread of domestic violence against women and about the protection capabilities at their disposal. The lack of recognition of all forms of gender-based violence, the trivial number of criminal sentences against persons who perform acts of domestic violence, the insufficient support offered to victims – including victim shelters, legal assistance, and counseling, and the lack of systematic databases on domestic violence cases on a national level, are a mere few of the many issues clearly pointing to the inevitable conclusion that the protection of women-victims of domestic violence is inadequate. Hence, the functionality and efficiency of both the existing legislation and the institutions in charge of protection and support of women – victims of domestic violence is being questioned, which is also the subject for analysis in this paper.